Cover Feature: Reactivity of the Indenyl Radical (C9H7) with Acetylene (C2H2) and Vinylacetylene (C4H4) (ChemPhysChem 11/2019). Issue 11 (4th June 2019) - Zhao, Long; Prendergast, Matthew B.; Kaiser, Ralf I.; Xu, Bo; Lu, Wenchao; Ablikim, Utuq; Ahmed, Musahid; Oleinikov, Artem D.; Azyazov, Valeriy N.; Mebel, Alexander M.; Howlader, A. Hasan; Wnuk, Stanislaw F.
Abstract : The Cover Feature illustrates that the resonantly stabilized 1‐indenyl radical does not undergo ring annulation upon reaction with acetylene to fluorene as postulated previously but forms 1‐ethynylindene. 1‐Indenyl could be part of yet unknown reaction pathways to molecular growth possibly involving radical–radical reactions. More information can be found in the Article by L. Zhao et al. onpage 1437 in Issue 11, 2019 (DOI:10.1002/cphc.201900052 ).